Statistical analysis of business cycle fluctuations in Poland before and after the crisis - Lukasz Lenart; Blazej Mazur; Mateusz Pipien (Institute of Economic Research (IER), 2015)
The main objective of the paper is to investigate properties of business cycles in Polish economy before and after the recent crisis. The essential issue addressed here is whether there exist statistical evidence that the recent crisis has affected the properties of the business cycle fluctuations. In order to improve robustness of the results we do not confine ourselves to any single inference method, but instead use different groups of statistical tools, including non-parametric methods based on subsampling and parametric Bayesian methods. We examine monthly series of industrial production (from January 1995 till December 2014), considering properties of cycles in growth rates and in deviations from long-run trend. Empirical analysis is based on the sequence of expanding-window samples, with the shortest sample ending in December 2006. The main finding is that the two frequencies driving business cycle fluctuations in Poland correspond to cycles with periods of 2 and 3.5 years, and (perhaps surprisingly) the result holds both before and after the crisis. We therefore find no support for the claim that features (in particular frequencies) that characterize Polish business cycle fluctuations have changed after the recent crisis. The conclusion is unanimously supported by various statistical methods that are used in the paper, however, it is based on the relative short series of the data currently available.
Keywords: C14; C46; E32; 330; APC processes; subsampling; Bayesian inference; global economic crisis; business cycle fluctuations